Electric field induced lattice strain in pseudocubic Bi(Mg1/2Ti1/2)O3-modified BaTiO3-BiFeO3 piezoelectric ceramics - Fujii, Ichiro; Iizuka, Ryo; Nakahira, Yuki; Sunada, Yuya; Ueno, Shintaro; Nakashima, Kouichi; Magome, Eisuke; Moriyoshi, Chikako; Kuroiwa, Yoshihiro; Wada, Satoshi (Applied physics letters, 2016)
Contributions to the piezoelectric response in pseudocubic 0.3BaTiO3-0.1Bi(Mg1/2Ti1/2)O3-0.6BiFeO3 ceramics were investigated by synchrotron X-ray diffraction under electric fields. All of the lattice strain determined from the 110, 111, and 200 pseudocubic diffraction peaks showed similar lattice strain hysteresis that was comparable to the bulk butterfly-like strain curve. It was suggested that the hysteresis of the lattice strain and the lack of anisotropy were related to the complex domain structure and the phase boundary composition.